Cryptography engineering : design principles and practical applications - Ferguson, Niels; Kohno, Tadayoshi; Schneier, Bruce , 1963- (Indianapolis, Indiana : Wiley, 2010)
Cryptography is vital to keeping information safe, in an era when the formula to do so becomes more and more challenging. This book shows you how to build cryptography into products from the start
1. Introduction -- 2. Message security -- 3. Key negotiation -- 4. Key management -- 5. Miscellaneous
"A fully updated version of ... Practical cryptography"--P. [4] of cover
Includes bibliographical references and index
Keywords: Computer security; Cryptography